Antioxidant Activity Analysis and Standardization of Parkia speciosa (Petai) Pods Ethanol Extract - Najma Annuria Fithri; Fitrya Fitrya; Tia Shabrina; Diva Yulanri (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2019)
Parkia speciosa (petai) pods are rarely used and considered as waste despite their phenolic and flavonoid content. Phenolic and flavonoid content in plants are known to exhibit antioxidant activity. Antioxidants are known to potentially act agains radical and mediate the damage by structural stabilization. This research was conducted to analyze the antioxidant potential of petai pods using DPPH method. Analysis showed the IC50 of petai pods ethanolic extract was 75.72 ppm, which indicate strong acting antioxidant. Standardization of extracts were determined to manage the quality of extract, including the analysis of density, water content, ash values, and quantification of total phenolic and flavonoid content. Research outcome indicate the extract retain its quality during storage and use which confrmed to standardization requirements of water content and ash values. Total phenolics and flavonoid obtained were 272.45 mg/gGAE and 243.2029 mg/gQE respectively. Based from this research, petai pods ethanolic extract present strong antioxidant activity which was contributed by high existing content of flavonoid and phenolic compounds.